1977
DOI: 10.1093/jnci/58.5.1449
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Pancreatic Carcinogen in Syrian Hamsters: N-Nitrosobis(2-oxopropyl)amine2

Abstract: N-Nitrosobis(2-oxopropyl)amine (BOP), a further postulated beta-metabolite of di-n-propylnitrosamine, induced a high incidence of pancreatic duct adenomas and adenocarcinomas as early as 13 weeks in Syrian hamsters receiving weekly sc injections for life and a few pancreatic adenomas, after 28 weeks, in those given a single sc dose. Compared to related compounds, N-nitrosobis(2-hydroxypropyl)amine and N-nitrosobis(2-acetoxy-propyl)amine which are also pancreatic carcinogens, BOP induced only a few neoplasms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(53 citation statements)
references
References 0 publications
2
48
0
3
Order By: Relevance
“…BOP is a potent carcinogen in the biliary tract and pancreas of hamsters (23). BOP-induced biliary carcinoma shows a histological resemblance to carcinoma in humans (22) and has thus made it possible to observe various early stage lesions which are often difficult to observe in humans (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…BOP is a potent carcinogen in the biliary tract and pancreas of hamsters (23). BOP-induced biliary carcinoma shows a histological resemblance to carcinoma in humans (22) and has thus made it possible to observe various early stage lesions which are often difficult to observe in humans (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ideal experimental model for pancreatic carcinoma should provide tumors of histologic type resembling human pancreatic carcinoma. As to induction of carcinoma originated from the pancreatic duct, Pour et al (1977) reported favorable results obtained by giving N-nitrosobis (2-oxopropyl) amine (BOP) to Syrian Golden hamsters. Dissin et al (1975) and Satake et al (1975) who embedded DMBA directly into the pancreas of SD rats also reported relatively favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…For investigating the mechanisms of the development of pancreatic cancer, an experimental pancreatic ductal carcinogenesis model has been established with the carcinogen N-nitrosobis(2-oxopropyl)amine (BOP) in hamsters (19)(20)(21)(22). This model provides unique characteristics that are similar to a sequence of well-characterized morphologic changes in the human pancreatic duct and frequently shows point mutations in codon 12 of the K-ras gene, in accordance with human findings (23,24).…”
mentioning
confidence: 87%